IDENTIFIKASI DAN UJI PENGENDALIAN HAMA DAUN JABON SECARA INVITRO - Ujang W. Darmawan; Agus Ismanto (Universitas Nusa Bangsa, 2014)
Identification and Control Test of Jabon Leaf Pest by Invitro One of problem in jabon (Neolamarckia cadamba [Roxb.] F. Bosser) plantation is defoliator. Identification and control effort are needed to counter this problem. This research was intended to identify pest species attacking plant and do efficacy test of several chemical and biological pesticides against the defoliator. The statistical method of efficacy was Completely Randomized Design (CRD). Two pesticides prophenophos (0,1%) and dimethoate (0,1%) as chemical based organic pesticides and Bacillus thuringiensis(0,5 g/l) as biological pesticide were tested against the defoliator. Data was analyzed using Anova and Tukey test at 95% confidence level. The result showed that pest was identified as Dysarthria quadricaudata. Chemical and biological pesticides were effective to control the pest.Keywords: Neolamarckia cadamba, Dysarthria quadricaudata, prophenophos, dimethoate, pest. ABSTRAK Salah satu persoalan pada hutan tanaman jabon (Neolamarckia cadamba [Roxb.] F. Bosser) adalah serangan hama perusak daun. Pengendalian diperlukan untuk mengatasi persoalan ini. Penelitian bertujuan untuk mengidentifikasi spesies hama dan melakukan efikasi beberapa jenis pestisida kimia dan organik terhadap hama ulat daun jabon (N. cadamba). Metode yang digunakan adalah rancangan acak lengkap. Dua jenis pestisida kimia berbahan profenofos (0,1%), dan dimetoat (0,1%) serta pestisida organik berbahan dasar Bacillus thuringiensis (0,5 gr/lt) diuji terhadap hama ulat daun. Data dianalisis menggunakan Anova dan uji Tukey (CI = 95%). Hasil penelitian menunjukkan bahwa spesies hama yang menyerang tanaman jabon adalah Dysarthria quadricaudata. Jenis pestisida tersebut efektif mengendalikan hama ulat daun jabon.Kata kunci: Neolamarckia cadamba, Dysarthria quadricaudata, profenofos. dimetoat, hama